SENYAWA SITOTOKSIK DARI FRAKSI DIKLOROMETANA DAUN PANDAN WANGI (Pandanus amaryllifolius Roxb.) TERHADAP SEL KANKER PAYUDARA MCF-7 - Ari Widiyantoro (Jambura Journal of Chemistry, 2023)
Pandan Wangi (Pandanus amaryllifolius Roxb.) is the plant that contains secondary metabolites with high antioxidant activity. These various activities include antibacterial, antidiabetic and hepatoprotective. This research was conducted to determine the cytotoxic activity and to determine the characteristics of isolates from dichloromethane fraction. This research was conducted in several stages including maceration, partitioning, and chromatography. The results showed that the isolate from dichloromethane fraction of pandan leaves had moderate cytotoxic activity against MCF-7 breast cancer cells with an IC50 of 155.0551 g/mL. The isolate from dichloromethane fraction was characterized 1H-NMR analysis (DMSO, 500 MHz), predicted as alkaloid group with a pyrrolidin skeleton. The chemical shift showed H 8.08 ppm (1H, s), 7.68 ppm (6H, m), 7.31 ppm (10H, m), 7.10 ppm (5H, s), 4.22 ppm (7H, m), 3.54 ppm (13H, s ), 3.36 ppm (11H, s), 3.16 ppm (2H, s), 2.64 ppm (2H, s), 2.36 ppm (2H, s), 1.98 ppm (1H, s), 1.65 ppm (12H, m), 1.45 ppm (12H, m), 1.29 ppm (19H, m), 1.17 ppm (5H, t), 1.10 ppm (4H, m), 1.06 ppm (3H, d), 0.99 ppm (6H, m), 0.79 ppm (24H, m) dan 0.51 ppm (17H, m).